Echinoidea from the Neogene of Portugal mainland - Pereira, Pedro (2017)
The Portuguese Neogene echinoid fauna is reviewed in order to establish a taxonomically standardised echinoid database. 41 taxa, including one new genus and new species, from the Burdigalian and Middle Miocene of the Lower Tagus Basin and Middle Miocene of Algarve and two taxa from the Middle Pliocene of Mondego Basin are described. 25 taxa are reported for the first time from Portugal mainland, while 22 of the previously reported Miocene species were excluded (for different motives) from the accepted species list. The list of Miocene species includes three cidarids [Eucidaris zeamays (Sismonda, 1842), Prionocidaris avenionensis (des Moulins, 1837) e P. sismondai (Mayer in Hartung, 1864)], five camarodonts [Genocidaris catenata (Desor in Agassiz & Desor, 1846), Genocidaris sp., Monilechinus portucallensis nov. gen. nov. sp., Psammechinus dubius dubius (Agassiz, 1840), Schizechinus sp.), six cassiduloids (Pliolampas elegantula ? (Cotteau, 1883), Studeria sp., Hypsoclypus subpentagonalis (Gregory, 1891), Echinolampas (E.) barcinensis Lambert, 1906, Echinolampas (E.) hemisphaerica (Lamarck, 1816), Echinolampas (E.) schultzi Kroh, 2005], eleven clypeasteroids [Clypeaster altus (Leske, 1778), C. campanulatus (Schlotheim, 1820), C. latirostris Michelin, 1861, C. marginatus Lamarck, 1816, C. olisiponensis Michelin, 1861, Echinocyamus sp. 1, Echinocyamus sp. 2, Parascutella lusitanica (de Loriol, 1896), P. smithiana (Agassiz, 1841), Parmulechinus sp., Amphiope bioculata (des Moulins, 1837)], and sixteen spatangoids [Opissaster cotteri de Loriol, 1896, Schizaster eurynotus Sismonda, 1841, Schizaster ? sp. 1, Ova karreri (Laube, 1869), Agassizia algarbiensis Ferreira, 1962, A. zitteli Fuchs, 1883, Pericosmus latus (Desor in Agassiz & Desor, 1847), Pericosmus sp. 1, Plagiobrissus vel Rhabdobrissus sp., Brissopsis crescentica Wright, 1855, B. ottnangensis Hoernes, 1875, Schizobrissus sp., Spatangus delphinus Defrance, 1827, Echinocardium olisiponensis Kotchetoff et al., 1975, Hemipatagus ocellatus (Defrance, 1827), Lovenia sp.]. The list of Pliocene taxa includes only camarodonts (Camarodonta indet.) and one clypeasteroid [Echinocyamus pusillus ? (Müller, 1776)].